Microarray Analysis of Antibodies Induced with Synthetic Antitumor Vaccines: Specificity against Diverse Mucin Core Structures. Issue 16 (23rd January 2017) - Pett, Christian; Cai, Hui; Liu, Jia; Palitzsch, Björn; Schorlemer, Manuel; Hartmann, Sebastian; Stergiou, Natascha; Lu, Mengji; Kunz, Horst; Schmitt, Edgar; Westerlind, Ulrika
Abstract: Glycoprotein research is pivotal for vaccine development and biomarker discovery. Many successful methodologies for reliably increasing the antigenicity toward tumor‐associated glycopeptide structures have been reported. Deeper insights into the quality and specificity of the raised polyclonal, humoral reactions are often not addressed, despite the fact that an immunological memory, which produces antibodies with cross‐reactivity to epitopes exposed on healthy cells, may cause autoimmune diseases. In the current work, three MUC1 antitumor vaccine candidates conjugated with different immune stimulants are evaluated immunologically. For assessment of the influence of the immune stimulant on antibody recognition, a comprehensive library of mucin 1 glycopeptides (>100 entries) is synthesized and employed in antibody microarray profiling; these range from small tumor‐associated glycans (TN, STN, and T‐antigen structures) to heavily extended O ‐glycan core structures (type‐1 and type‐2 elongated core 1–3 tri‐, tetra‐, and hexasaccharides) glycosylated in variable density at the five different sites of the MUC1 tandem repeat. This is one of the most extensive glycopeptide libraries ever made through total synthesis. On tumor cells, the core 2 β‐1, 6‐ N ‐acetylglucosaminyltransferase‐1 (C2GlcNAcT‐1) is down‐regulated, resulting in lower amounts of the branched core 2 structures, which favor formation of linear core 1 or core 3 structures, and in particular, truncated tumor‐associated antigen structures. The core 2 structures are commonly found on healthy cells and the elucidation of antibody cross‐reactivity to such epitopes may predict the tumor‐selectivity and safety of synthetic vaccines. With the extended mucin core structures in hand, antibody cross‐reactivity toward the branched core 2 glycopeptide epitopes is explored. It is observed that the induced antibodies recognize MUC1 peptides with very high glycosylation site specificity. The nature of the antibody response is characteristically different for antibodies directed to glycosylation sites in either the immune‐dominant PDTR or the GSTA domain. All antibody sera show high reactivity to the tumor‐associated saccharide structures on MUC1. Extensive glycosylation with branched core 2 structures, typically found on healthy cells, abolishes antibody recognition of the antisera and suggests that all vaccine conjugates preferentially induce a tumor‐specific humoral immune response. Abstract : Antibody mapping : A library of mucin glycopeptides was prepared for the evaluation of antibodies generated from synthetic vaccines and directed against tumor‐associated mucin‐1 glycoproteins. All antibody sera showed high reactivity to the tumor‐associated saccharide structures on MUC1. Extensive glycosylation with branched core 2 structures, typically found on healthy cells, abolishes antibody recognition of the antisera, and suggests that all vaccine conjugates preferentially induce a tumor‐specific humoral immune response.